Effect of obesity on COVID-19 disease severity in children - Yakup Çağ; Ayşe Karaaslan; Aslı A Çıkrıkçıoğlu; Mehmet T Köle; Ceren Çetin; Yasemin Akın (Journal of Infection in Developing Countries)
Introduction: Coronavirus disease 2019 (COVID-19) has caused many injuries and deaths worldwide. Obesity is reported to be an important risk factor for severe COVID-19, although the underlying mechanism is not fully understood. The present study aimed to determine whether obesity or being overweight is associated with the clinical course and severity of COVID-19 in children.